EVALUASI PERATURAN DAERAH NOMOR 2 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU (Studi Kasus: Parkir Pada Badan Jalan) - Yuke Nurhasni; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Not enough facility of parking, causing government of Pekanbaru City make the road as location of parking facility because the government see there is potential that can help regional revenue by organize collecting of parking retribution. Implementation on street parking is regulated in Perda Nomor 2 tahun 2009 tentang Lalu Lintas dan Angkutan Jalan di Kota Pekanbaru. But acceptance of parking retribution is not stable in the last 5 years because of increased and decreased, and did not reach the target. The purpose of this research was to evaluate Peraturan Daerah Nomor 2 tahun 2009 tentang Lalu Lintas dan Angkutan Jalan di Kota Pekanbaru spesifically for organizing on street parking and to know the factors that influence the evaluation of Peraturan Daerah Nomor 2 tahun 2009 tentang Lalu Lintas dan Angkutan Jalan di Kota Pekanbaru spesifically for organizing on street parking.Dunn In theory, there are 6 (six) evaluation indicators, that is: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy of policy. The method used is descriptive qualitative with purposive sampling technique. Informants in this research is Dinas Pehubungan, Komunikasi dan Informatika Kota Pekanbaru, Traffic Observer of Pekanbaru City, Coordinator Parking, Parking Attendant and Public Parking Service Users.Based on research that has been conducted by the authors, Peraturan Daerah Nomor 2 tahun 2009 tentang Lalu Lintas dan Angkutan Jalan di Kota Pekanbaru which arrange about organizing on street parking has not been successful categorized and not appropriate with this time. In this research, it looks very much difference between expectations and reality. This conclusion is based on the concept of Dunn evaluation criteria. It also found the factors that influence policy evaluation, that is traffic growth factors, availability of land, and public participation.Keywords: Evaluation, Parking, On Street Parking